Epidemiological Change and Chronic Disease in Sub-Saharan Africa Social and historical perspectives - Vaughan, Megan; Adjaye-Gbewonyo, Kafui; Mika, Marissa (UCL Press, 2021)
Epidemiological Change and Chronic Disease in Sub-Saharan Africa offers new and critical perspectives on the causes and consequences of recent epidemiological changes in sub-Saharan Africa, particularly on the increasing incidence of so-called 'non-communicable' and chronic conditions. Historians, social anthropologists, public health experts and social epidemiologists present important insights from a number of African perspectives and locations to present an incisive critique of 'epidemiological transition' theory and suggest alternative understandings of the epidemiological change on the continent. Arranged in three parts, 'Temporalities: Beyond Transition', 'Numbers and Categories' and 'Local Biologies and Knowledge Systems', the chapters cover a broad range of subjects and themes, including the trajectory of maternal mortality in East Africa, the African smoking epidemic, the history of sugar consumption in South Africa, causality between infectious and non-communicable diseases in Ghana and Belize, the complex relationships between adult hypertension and paediatric HIV in Botswana, and stories of cancer patients and their families as they pursue treatment and care in Kenya. In all, the volume provides insights drawn from historical perspectives and from the African social and clinical experience to offer new perspectives on the changing epidemiology of sub-Saharan Africa that go beyond theories of 'transition'. It will be of value to students and researchers in Global Health, Medical Anthropology and Public Health, and to readers with an interest in African Studies.